Risky Driving Behaviours and Their Impact on Road Traffic Accidents: Insights from Commercial Bus Drivers in Nigeria - Hassan, Sitti Asmah; Olusegun, Olusegun Austine Taiwo; Mohsin, Rahmat Bin Mohsin; Mahmud, Norashikin Mahmud (International Journal of Integrated Engineering, 2025)
Public transport safety mainly depends on bus drivers due to their crucial roles. Therefore, understanding commercial bus drivers’ driving behaviours can aid in determining areas that need urgent attention. The study examines the influence of their risky driving behaviour on road traffic accidents (RTAs) and the moderating effect of the bus drivers’ driving experience and education level. The validity results showed that Driver Behaviour Questionnaire (DBQ) is reliable and valid for commercial bus drivers. Also, through the structural model assessment of risky driving behaviour, the findings reveal that violations (β = 0.121, p < 0.05) and erors (β = 0.094, p < 0.05) are significant predictors of road traffic accidents among commercial bus drivers, explaining 4% of the variance in accident involvement. In other words, the study revealed a significant influence of driving violations and errors on RTA, while inattention errors were insignificant. The Importance-performance map indicates that serious measures and attention are needed to reduce driving violations. Additionally, driving experience and educational level did not moderate the relationship between risky driving behaviour and RTA. The study offers unique insights by identifying critical driving behaviour that demands strategic intervention from policymakers, driver trainers, and transport employers.